Could sports biomechanics provide the missing pieces to the talent identification and development puzzle? - Glazier, P. S. (Routledge handbook of talent identification and development in sport, 2014)
Biomechanics has been conspicuously absent, not only from the vast majority of talent identification and development (TID) programmes in sport, but also from almost all scientific expositions on the topic. The omission of a biomechanical component from many TID programmes appears to be a major shortcoming of these initiatives, especially given that, in many sports, one of the strongest indicators of `talent` is the technical proficiency (i.e., coordination and control) with which motor skills integral to those sports are performed. This chapter examines some of the main issues that have prevented biomechanics from occupying a more central role in TID in sport and discusses if, and how, these barriers may be overcome. It is concluded that biomechanics could help to identify and develop talent in sport but further research is required to establish what biomechanical characteristics define expert sports performance and how changes in organismic (e.g., anatomical, morphological, neurophysiological) constraints associated with physical maturation and growth impact on the coordination and control of sports techniques. This research would benefit from adopting an interdisciplinary approach, integrating biomechanical measurements with motor control theory, and will require the adoption of innovative techniques and methods that have only been fleetingly used in previous biomechanical investigations of sports techniques.